The Toxic Effects of Ppz1 Overexpression Involve Nha1-Mediated Deregulation of K+ and H+ Homeostasis - Albacar, Marcel; Sacka, Lenka; Calafí, Carlos; Velázquez, Diego; Casamayor, Antonio; Ariño, Joaquín; Zimmermannova, Olga (Journal of fungi (Basel, Switzerland), 2021)
The alteration of the fine-tuned balance of phospho/dephosphorylation reactions in the cell often results in functional disturbance. In the yeast Saccharomyces cerevisiae, the overexpression of Ser/Thr phosphatase Ppz1 drastically blocks cell proliferation, with a profound change in the transcriptomic and phosphoproteomic profiles. While the deleterious effect on growth likely derives from the alteration of multiple targets, the precise mechanisms are still obscure. Ppz1 is a negative effector of potassium influx. However, we show that the toxic effect of Ppz1 overexpression is unrelated to the Trk1/2 high-affinity potassium importers. Cells overexpressing Ppz1 exhibit decreased K+ content, increased cytosolic acidification, and fail to properly acidify the medium. These effects, as well as the growth defect, are counteracted by the deletion of NHA1 gene, which encodes a plasma membrane Na+, K+/H+ antiporter. The beneficial effect of a lack of Nha1 on the growth vanishes as the pH of the medium approaches neutrality, is not eliminated by the expression of two non-functional Nha1 variants (D145N or D177N), and is exacerbated by a hyperactive Nha1 version (S481A). All our results show that high levels of Ppz1 overactivate Nha1, leading to an excessive entry of H+ and efflux of K+, which is detrimental for growth.
Keywords: Saccharomyces cerevisiae; intracellular pH; Nha1; K+ transport; Ppz1 phosphatase; cation homeostasis